Spatiotemporal analysis of ecological vulnerability along Bangladesh-China-India-Myanmar economic corridor through a grid level prototype model - Yuan Jin (Elsevier, 2021)
Bangladesh-China-India-Myanmar economic corridor, a critical part of the Belt and Road Initiative program, is subject to the impact of various natural disasters and intense human activities, which have led to serious ecological vulnerability. This study proposed a prototype model using geographically weighted principal component analysis to quantify ecological vulnerability at the grid level, and an analysis was conducted on the dynamic changes of ecological vulnerability along Bangladesh-China-India-Myanmar economic corridor during 2005–2015. An indicator system for 23 spatial variables was established based on Driver-Pressure-State-Impact-Response framework to calculate the ecological vulnerability index. The cluster principle was adopted to split the ecological vulnerability into five vulnerability levels, namely, potential, light, medium, heavy, and very heavy. Given the spatial recognition of ecologically vulnerable areas along Bangladesh-China-India-Myanmar economic corridor, several suggestions on ecological management were offered. As revealed from the results, the ecological vulnerability has been rising progressively, particularly in the mountainous areas, and most of the protected areas are at medial to very heavy vulnerability level. The ecological vulnerability was tightly correlated with vulnerability events and impacts. As suggested from the results, ecological restoration and protection measures should be strictly implemented to minimize the adverse impact on the protected areas under the construction of economic corridor. Our results indicated that the geographically weighted principal component analysis can effectively quantify environmental vulnerability, and these space management policies has implications for ecological protection, resource utilization, and sustainable development in other similar regions.